Samvete i Sverige Om frihet och lydnad från medeltiden till idag - Lindkvist, Linde; Ljungberg, Johannes (Kriterium, 2021)
In recent years, ideas of conscience and the liberty of conscience have become ever more salient in public discourse. Historically, these concepts have been used to mark out a certain scope of freedom and protection in moral, political and legal conflicts. In our time, individual conscience is frequently used to legitimate objections to, for instance, military service and medical interventions like abortion and vaccination. So too in Sweden - a country widely described as one of the most modern and secularized societies in the world. In this volume, a group of researchers in history, human rights, law, ethics and sociology of religion address some of the most central issues around conscience and the liberty of conscience in Sweden from the middle ages to the present. By situating conscience and liberty in wider intellectual, social and political settings, the essays provide alternative ways of thinking about the most intractable problems surrounding these concepts - the relationship between law and morality, the tension between individual and collective freedom, as well as the role of religion in public affairs. This volume will create new avenues of research for scholars and students interested in challenges related to conscience and liberty: both those in ethics, politics and law seeking a historical perspective, and those in history who want to tie their studies to the present.